P245 Pulmonary function tests in asymptomatic patients with inflammatory bowel disease: preliminary results of a single-centre cohort study. (25th January 2019) - Fragaki, M; Pasparaki, E; Bibaki, E; Kounalakis, G; Ferdoutsis, E; Paspatis, G; Meletis, G; Karmiris, K
Abstract: Background: Pulmonary dysfunction is frequently underestimated in inflammatory bowel disease (IBD) patients. The aim of this study was to investigate pulmonary function in IBD patients and identify possible risk factors for pulmonary dysfunction. Methods: Consecutive informed and consented IBD patients < 60 years old followed up in our centre underwent pulmonary function tests (PFTs) during their regular follow-up visit. Measurements conducted were forced vital capacity (FVC), forced expiratory volume in one sec (FEV1) and maximal mid-expiratory flow (MMEF 75/25). Exclusion criteria were an acute or chronic respiratory disease as well as the presence of an established pulmonary extra-intestinal manifestation. Results: Sixty-four IBD patients have been enrolled so far (males: 53.1%, Crohn's disease: 62.5%, mean age at IBD diagnosis: 35.5 years [SD ± 12.7], median [IQR] duration of IBD: 7.2 months [3.3–12.0], extraintestinal manifestations: 39.1%). Seventeen patients (26.5%) had never smoked with the rest being either active (42.2%) or ex- (31.3%) smokers. Twenty-four patients (37.5%), including 6/17 (35.3%) non-smokers, revealed abnormal PFTs (males:14/24, Crohn's disease: 16/24); 7 (29.1%) exhibited a restrictive pattern, 7 (29.1%) an obstructive pattern (57.1% mild and 42.9% moderate GOLD stage) and 10 (41.7%) small airway disease. Interestingly, appendectomy was more commonly reported in non-smokers with abnormal LFTs compared with those without ( p = 0.04). IBD was active at baseline in 4/24 and extraintestinal manifestations were present in 10/24 patients. Anti-TNFα agents were administered in 11/24 patients. Three patients were under combination therapy with an IMS. There was no association of abnormal PFTs with gender, disease sort or location or behaviour or activity, tonsillectomy, IBD therapy either as monotherapy or as combination therapy and the presence of anaemia. Conclusions: More than one-third of our IBD patients in total and of non-smokers in particular demonstrate abnormal LFTs measured in a random outpatient visit without any symptoms, signs or history of respiratory disease. Appendectomy was associated with LFTs abnormality in non-smokers perhaps revealing an immunologic defect influencing the development of obscure primary or secondary pulmonopathy on the background of IBD. These results should of course be interpreted with caution for the time being, while awaiting those of a larger cohort.